2006
DOI: 10.1007/s10460-005-6110-9
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Farmers’ Preference and use of Commercial and Self-compounded Feeds in Oyo Area of Oyo State, Nigeria

Abstract: This study investigated poultry farmers' perceptions, preferences, and use of commercially compounded and self-compounded feeds in the Oyo Area of Oyo State, Nigeria. Data were collected from 120 poultry farmers through a structured interview schedule. The study concluded that poultry farmers prefer and use self-compounded feeds (SCF) instead of commercially compounded feeds (CCF) because (a) self-compounded feeds are of better quality than commercially compounded feeds, (b) there are no quality control measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
3
1
Order By: Relevance
“…Cost evaluation revealed that the self-formulated diet was cheaper to compound and had least cost of N 60.00 / kg feed. This finding is similar to report by Apantaku et al (2006) in Oyo area where poultry farmers prefer and use self-formulated feeds instead of commercially compounded feeds, which is perceived to be of higher quality and lower cost. The highest feed cost of N 90.00/kg was recorded on T3 diet.…”
Section: Discussionsupporting
confidence: 89%
“…Cost evaluation revealed that the self-formulated diet was cheaper to compound and had least cost of N 60.00 / kg feed. This finding is similar to report by Apantaku et al (2006) in Oyo area where poultry farmers prefer and use self-formulated feeds instead of commercially compounded feeds, which is perceived to be of higher quality and lower cost. The highest feed cost of N 90.00/kg was recorded on T3 diet.…”
Section: Discussionsupporting
confidence: 89%
“…The result implies that majority (61.0%) of the poultry farmers in the study area used hybrid feed because hybrid feed is as a balance poultry feed. This result contrast that of Akpantaku et al (2006) who reported that farmers in Oyo State preferred self-compounded feed instead of commercially compounded feed because they are of better quality. Source: Field survey, 2020…”
Section: Results and Discussion Feed Type Used Among Poultry Farmerscontrasting
confidence: 91%
“…However, in a recent study of (peri-)urban livestock production in Niamey, Diogo et al ( 2010 ) observed that the quantity of feed and nutrients offered to animals by far exceeded their requirements and finally ended up at the dung heap in form of faeces, urine and feed refusals. The high costs of commercial poultry feeds and negative experiences of poultry farmers with respect to the quality of these feeds (Apantaku et al 2006 ) were probably the main reasons for the preference of self-compounded feeds.…”
Section: Discussionmentioning
confidence: 99%